A simple clinical model predicts incident hepatic steatosis in a community-based cohort: The Framingham Heart Study - Long, Michelle T. (Liver Int, 2018)
BACKGROUND AND AIMS: The factors associated with incident hepatic steatosis are not definitively known. We sought to determine factors associated with incident hepatic steatosis, as measured on computed tomography, in the community. METHODS: We studied Framingham Heart Study participants without heavy alcohol use or baseline hepatic steatosis who underwent computed tomography scans between 2002–2005 (baseline) and 2008–2011 (follow-up). We performed a stepwise logistic regression procedure to determine the predictors associated with incident hepatic steatosis. RESULTS: We included 685 participants (mean age: 45.0 ± 6.2 years, 46.8% women). The incidence of hepatic steatosis in our sample was 17.1% over a mean 6.3 years of follow-up. Participants who developed hepatic steatosis had more adverse cardio-metabolic profiles at baseline compared to those free of hepatic steatosis at follow-up. Multivariable stepwise regression analysis showed that a simple clinical model including age, sex, body mass index, alcohol consumption and triglycerides was predictive of incident hepatic steatosis (C statistic = 0.791, 95% CI: 0.748–0.834). A complex clinical model, which included visceral adipose tissue volume and liver phantom ratio added to the simple clinical model, and had improved discrimination for predicting incident hepatic steatosis (C statistic = 0.826, 95% CI: 0.786–0.866, P < .0001). CONCLUSIONS: The combination of demographic, clinical and imaging characteristics at baseline was predictive of incident hepatic steatosis. The use of our predictive model may help identify those at increased risk for developing hepatic steatosis who may benefit from risk factor modification although further investigation is warranted.